2015
DOI: 10.1111/tops.12146
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Search in the Remote Associates Test

Abstract: Searching through semantic memory may involve the use of several retrieval cues. In a verbal fluency task, the set of available cues is limited and every candidate word is a target. Individuals exhibit clustering behavior as predicted by optimal foraging theory. In another semantic search task, the remote associates task (RAT), three cues are presented and a single target word has to be found. Whereas the task has been widely studied as a task of creativity or insight problem solving, in this article, the RAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 36 publications
(55 reference statements)
7
71
1
Order By: Relevance
“…Considering this same sequential dependence in creative search tasks like the RAT potentially yields a different interpretation of Davelaar's results. Like Davelaar (), we (Smith et al., ) found that responses are likely to switch at near‐chance levels between “patches” of words defined by the semantic associates of the individual cues. On top of this, Davelaar finds that the cues combine in a superadditive fashion, since the probability of producing a word in response to all three RAT cues is greater than an additive combination of producing that word in response to the three cues individually.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Considering this same sequential dependence in creative search tasks like the RAT potentially yields a different interpretation of Davelaar's results. Like Davelaar (), we (Smith et al., ) found that responses are likely to switch at near‐chance levels between “patches” of words defined by the semantic associates of the individual cues. On top of this, Davelaar finds that the cues combine in a superadditive fashion, since the probability of producing a word in response to all three RAT cues is greater than an additive combination of producing that word in response to the three cues individually.…”
supporting
confidence: 65%
“…
How do we search through our vast stores of knowledge to retrieve information demanded by the context and task at hand? Davelaar (2015) finds that the words people report while searching for one word that is meaningfully associated with three cues (e.g., cues: comb, moon, dew; answer: honey; the Remote Associates Test, RAT) seem to be drawn from a superadditive combination of the semantic associations of the three cues, rather than "clustered" in pre-existing patches as expected by previous theories of semantic search (e.g., Troyer, Moscovitch, & Winocur, 1997). Although we found similar behavior in the same paradigm (Smith, Huber, & Vul, 2013), our interpretation hinged on a different property of search: There is sequential dependence between words reported during the search process.
…”
mentioning
confidence: 99%
“…In the RAT's compound-word version (24) participants are presented with three cue words (e.g., walker/main/sweeper) and are asked to find a solution or target word which makes a compound word with each of these three words (e.g., solution is street: streetwalker/main street/ street sweeper). People tend to seek the solution word by searching in the pool of semantically related words to the presented cues (25)(26)(27). However, there is a trap in this habitual thinking: When two cue words have close semantic association with a word that is not the correct solution this can get in the way of the true solution, thereby acting as an important distractor which attracts internal attention (6).…”
Section: Methodsmentioning
confidence: 99%
“…Spectral power in each frequency immediately following the RAT item presentation (whole trial and also 0-1 s) was log-transformed (base 10) due to its positively skewed distribution and divided by the total (average) . Therefore, we analyzed relative power in each frequency band, theta (4-8 Hz), alpha (8-12 Hz), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), as well as the IAF, defined as the frequency with the highest power from 8 to 12 Hz (±2 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…A similar finding was observed in our study on radiological diagnosis 1 . The implicit organization of semantic networks and lexical semantic associative processes have been studied with different models 25, 26 .…”
Section: Discussionmentioning
confidence: 99%